Orthogonal Latin Square Constructions - Ibrahim, Haslinda (Universiti Teknologi MARA, 2004)
The 18th-century mathematician Euler credited with the development of the latin square combinatorial design, was responsible for numerous theorems and constructions of latin squares. MacNeish, another prominent mathematical scholar, further developed the latin square conjecture in the 1920s, but more recent work by Bose, Shrikhande and Parker led to the collapse of Euler and MacNeish conjectures. This paper illustrates the sequential unfolding of our understanding of orthogonal latin square constructions